Influencing Factor Analysis on the Fractured Tight Sandstone Gas Reservoir Characteristics: A Case Study of Bozi 3 Gas Reservoir in the Tarim Basin - Liu, Zhaolong; Zhang, Yongling; Zhang, Yongzhong; Zhao, Libin; Peng, Peng; Liu, Hualin; Chang, Baohua; Huang, Weigang; Zhou, Peng (Frontiers in Earth Science, 2022)
The Bozi 3 gas reservoir in the Tarim Basin is a typical ultra-deep fractured tight sandstone gas reservoir, in which the main formations are the Cretaceous Bashijiqike Formation and the Baxigai Formation. The reservoir has the characteristics of deep burial, tight reservoir matrix, well-developed fractures, large differences in well productivity, and regional pressure distribution. These characteristics bring development challenges in well deployment, production allocation, gas production rate optimization, and production improvement. The main reservoir of Bozi 3 is deposited in the braided river delta, fan delta, and shallow lake environment with adequate provenance and a strong hydrodynamic environment, which provides favorable depositional conditions for the formation of thick sandbodies. Although the buried depth of the Bozi 3 gas reservoir is over 6,000 m, it has undergone an evolutionary process of long-term shallow burial in the early stage and rapid deep burial in the late stage, which protects the primary pore, and the finally formed reservoir has the characteristics of an extra-low pore and ultra-low permeability pore structure. Late tectonic movements caused the Bozi 3 gas reservoir to experience strong uplift under a strong nappe-thrust environment, forming a large number of high-angle fractures around the faults. Although the fracture distribution is inhomogeneous, tensile fractures at the top anticline have a low-filling degree and good effectiveness, which effectively improve Bozi 3 reservoir properties. Through analysis of the reservoir characteristics and influencing factors of the Bozi 3 gas reservoir, it is concluded that the difference in reservoir characteristics is the main reason for the large difference in production of adjacent wells and zonal distribution of formation pressure at the early development. This study can also provide a reliable geological basis for well deployment, production allocation rationalization, and gas production rate optimization in the study area.